ضمانات الصفقات العمومية في المرسوم الرئاسي 15/247 المتضمن تنظيم الصفقات العمومية وتفويضات المرفق العام - لعمري، محمد Lameri, Mohammed (المركز الجامعي علي كافي تندوف, 2023)
تكتسي فكرة الضمان في مجال الصفقات العمومية مفهوم واسع فأي موقف أو إجراء تتخذه الإدارة يمكن اعتباره تصرف مشروع لما تملكه من امتيازات السلطة العامة كونها المسئولة على صرف المال العام لإشباع حاجات المصلحة العامة. ونظرا لعدم توازي الحقوق بين أطراف عقد الصفقات العمومية خاصة ضعف مركز المتعامل المتعاقد يجعله متخوفا من ظهور أي طارئ أو تعسف يعسر من أداءه لالتزاماته أو ينقص من حقوقه، لذا جاء المرسوم الرئاسي 247/15 المنظم للصفقات العمومية وتفويضات المرفق العام بضمانات حمائية تكفل حقوق الأطراف عبر مراحل تنفيذ العقد The idea of security guarantee in the field of public procurement has a broad concept any position or action taken by the administration can be considered a legitimate act because of the privileges of the public authority as it is responsible for the spending public funds to satisfy the needs of the public interest. In view of the imbalance of rights between the party to the public procurement contract which made the contractor weak making him afraid of the emergence of any emergency or arbitrariness that impairs the performance of his obligations or diminishes his rights contract. can not resist it only which protection guarantees legally guaranteed in the form of pre-agreed items derived from presidential Decree 15/247 containing the organization of public procurements and mandates of the general attachment are protected by safeguards guaranteeing the rights of the through the implementation stages of the contract.
Keywords: الصفقات العمومية -- الضمانات الإدارية -- العقود الإدارية -- الالتزامات التعاقدية -- القضاء الإداري